2019
DOI: 10.1126/scisignal.aaw3159
|View full text |Cite
|
Sign up to set email alerts
|

Host mitochondria influence gut microbiome diversity: A role for ROS

Abstract: Changes in the gut microbiota and the mitochondrial genome are both linked with the development of disease. To investigate why, we examined the gut microbiota of mice harboring various mutations in genes that alter mitochondrial function. These studies revealed that mitochondrial genetic variations altered the composition of the gut microbiota community. In cross-fostering studies, we found that although the initial microbiota community of newborn mice was that obtained from the nursing mother, the microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 58 publications
7
103
0
Order By: Relevance
“…This may amplify the effect of eATP on tight junctions. On the other hand, it has been shown that functional changes in mitochondria directly change the microbiome [103] and intestinal epithelial cell and mucosal function at the host-microbe interface [104]. The inhibition of mitochondrial function by systemic eATP shown in this study might therefore be a direct cause of intestinal epithelial cell functional changes that lead to chronic changes in the microbial ecology of the gut.…”
Section: Microbiomementioning
confidence: 61%
“…This may amplify the effect of eATP on tight junctions. On the other hand, it has been shown that functional changes in mitochondria directly change the microbiome [103] and intestinal epithelial cell and mucosal function at the host-microbe interface [104]. The inhibition of mitochondrial function by systemic eATP shown in this study might therefore be a direct cause of intestinal epithelial cell functional changes that lead to chronic changes in the microbial ecology of the gut.…”
Section: Microbiomementioning
confidence: 61%
“…This increase in O 2 may provide a potential mechanistic explanation for changes in microbiome associated with GVHD and IBD. The change in O 2 levels might lead to dysbiosis with loss of microbial diversity, decrease in commensals such as obligate anaerobes and shift towards to aerobes and pathobionts in the microbiome of patients with GVHD and IBD 43 44 45 46 47 48 49 50 51 52 53 54 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs as a result of an imbalance between reactive oxygen species and the defence system responsible for ROS elimination. Long-term high-fat diet induces oxidative stress in colon [11,12] besides inducing bacterial dysbiosis by changing the redox status [13,14]. Bacteria with higher resistance to oxidative stress (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise role of gut microbiota in obesity is still unknown, a dietary factor, especially high fat consumption, is considered to play an important role in linking obesity with gut microbiota. High-fat diet is known to increase the levels of oxidative stress in colon [11,12] and affect the composition of colonic microbiota [13,14]. Abdominal fat tissue is also known to directly increase reactive oxygen species (ROS) levels [15,16] Lactobacillus has been reported to show high diversity in resistance to oxidative stress across species [17,18] and strains [19], based on catalase activity.…”
Section: Introductionmentioning
confidence: 99%